Radical irradiation of the prostate. Combination of percutaneous irradiation and irradiation with LDR Ir-192 implants - Kragelj, Borut (Radiology and oncology (Ljubljana), 2001)
Background. The irradiation of the carcinomas of the prostate with the doses above the tolerable ones of standard radiotherapy improves the local control of the disease. The aim of this study is to determine the acute toxicity and tolerability of the high-dose prostate irradiation combining external beam radiotherapy (EBRT) and interstitial low dose rate (LDR) brachyradiotherapy (BRT) Ir-192 of the prostate. Material and methods. We examined medical records of 8 patients with localized carcinoma of the prostate (T2-T3 No-x Mo)treated from August 1999 until February 2000. The initial PSA was 2.7-37.5 ng/ml (median 13.7) and Gleason score 4-9 (median 7). Radiotherapy consisted of 48.6-50.4 Gy of EBRT to the prostate and seminal vesicles (4 patients) or the whole pelvis (4 patients) and 20.0-28.0 Gy of interstital LDR Ir-192 BRT given as a single fraction, fluoroscopic guided transperineal Implantation of the prostate. The cumulative doses of percutaneous and interstitial irraditations to the prostate were 68.6 - 79.1 Gy. Results. Acute toxic effects of irradiation though observed in all patients were of only mild intensity. According to the RTOG criteria, 20/30 toxicities were assessed as grade 1, 9/30 as grade 2, and 1/30 as grade 3. In none of the patients, toxic effects required any specific modification of the treatment regimen. Conclusions. The very first experiences indicate moderate toxicity and optimaltolerance of the treatment by patients. An improvement of implantation techniques may be expected with regular CT controls of the implants and extra attentive care of the implants in the urethra region.
Keywords: Brachytherapy; Iridium radioisotopes; prostata; prostate; Prostatic neoplasms; radioterapija; Radiotherapy; Radiotherapy dosage; rak (medicina); therapy; zdravljenje